2020
DOI: 10.1159/000508110
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Perfusion Is Associated with Endothelial Dysfunction Markers in Major Depressive Disorder

Abstract: <b><i>Background:</i></b> Major depressive disorder (MDD) is an important independent risk factor for cardiovascular disease. Cumulative data suggest that depressive patients exhibit derangement in regional cerebral blood flow (rCBF), although underlying mechanisms remain mostly unknown. Endothelial dysfunction (ED), defined as different forms of abnormal endothelial activity, plays a key role in the pathogenesis of vascular disease. ED is associated with several clinical conditions cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Sertraline has been found to lessen increased platelet secretion found among depressed patients; however, both groups of our patients were receiving SSRIs [79]. Endothelial dysfunction is also consistently present in MDD, as well as platelet activation and other peripheral inflammatory and oxidative stress biomarkers associated to rCBF changes after SSRIs therapy, as demonstrated by our group [80, 81].…”
Section: Discussion/conclusionsupporting
confidence: 62%
“…Sertraline has been found to lessen increased platelet secretion found among depressed patients; however, both groups of our patients were receiving SSRIs [79]. Endothelial dysfunction is also consistently present in MDD, as well as platelet activation and other peripheral inflammatory and oxidative stress biomarkers associated to rCBF changes after SSRIs therapy, as demonstrated by our group [80, 81].…”
Section: Discussion/conclusionsupporting
confidence: 62%
“…Such biomarkers of endothelial dysfunction include endothelin-1 (ET-1), circulating endothelial cells, endothelial microparticles, endoglin, etc. [ 100 ], plasma soluble intercellular adhesion molecules (siCAM), or high-sensitive C-reactive particles (hs-CRP) [ 101 ]. A genome-wide association study (GWAS) suggested a potential role of vascular endothelial growth factor (VEGF) in depression development [ 102 ].…”
Section: Impaired Cerebral Hemodynamicsmentioning
confidence: 99%
“…Furthermore, endothelial dysfunction was associated with a persistent course of depression [ 104 ]. More recent evidence for the role of systemic damage of the endothelium was found in a study showing that markers for endothelial dysfunction were associated with reduced CBF in LLD patients [ 101 , 105 ]. In conclusion, these studies suggest that macro- and microvascular dysfunctions causing impaired cerebral hemodynamics/reduced perfusion play a role in the development of LLD.…”
Section: Impaired Cerebral Hemodynamicsmentioning
confidence: 99%
“…Additionally, perfusion abnormality in BA 23 increased in both groups but more in the placebo group. In one of our previous studies published recently, a significant association between endothelial dysfunction markers and changes in rCBF was observed in another group of MDD patients not taking any specific medication [76]. This suggests that the systematic damage or activation of the endothelium may be contributing to the observed perfusion abnormality.…”
Section: Feature Selectionmentioning
confidence: 68%